An In‐Depth Analysis of Patient‐Reported Outcomes in Patients With Chronic Hepatitis C Treated With Different Anti‐Viral Regimens. (June 2016) - Younossi, Zobair M; Stepanova, Maria; Henry, Linda; Nader, Fatema; Hunt, Sharon
Abstract : OBJECTIVES: Interferon‐ and ribavirin (RBV)‐containing regimens negatively impact patients' experience. The aim of this study was to quantify the impact of different anti‐viral regimens for hepatitis C on patients' work productivity, fatigue, and other patient‐reported outcomes (PROs). METHODS: The PRO data from multicenter multinational phase 3 clinical trials of sofosbuvir with and without interferon or RBV were retrospectively used. Treatment regimens were classified as interferon+RBV‐containing, interferon‐free RBV‐containing, and interferon‐free RBV‐free. Four PRO instruments (SF‐36, CLDQ‐HCV, FACIT‐F, and WPAI:SHP) were administered to subjects at baseline, during, and up to 24 weeks after treatment. RESULTS: We included 3, 425 subjects with chronic hepatitis C infection with PRO data. Patients were 62.8% male, 62.2% treatment naive, 18.1% with cirrhosis, and 72.9% with HCV genotype 1. Of the study participants, 546 received interferon+RBV+sofosbuvir, 1, 721 received sofosbuvir+RBV, and 1, 158 received interferon‐ and RBV‐free ledipasvir+sofosbuvir. At baseline, there were no difference in PROs between treatment groups (all P >0.01). During treatment, the decrements in PROs were up to −23.6% for the interferon+RBV group, up to −7.0% in the sofosbuvir+RBV group, whereas there was an improvement of up to +11.6% in the interferon‐free RBV‐free group (all P <0.0001). In multivariate analysis, the use of interferon was independently associated with up to −26.0% worsening of the PRO scores during treatment and the use of RBV with up to −9.0% worsening. After 12 weeks post‐treatment, in patients with sustained virologic response‐12, improvements were observed regardless of the regimen, and these improvements continued to increase by week 24 of follow‐up. CONCLUSIONS: The use of interferon‐ and RBV‐free regimens for HCV is associated with better patients' experience and work productivity during treatment.